Impact of Gross Strap Muscle Invasion on Outcome of Differentiated Thyroid Cancer: Systematic Review and Meta-Analysis - Zhang, Li; Liu, Jia; Wang, Peisong; Xue, Shuai; Li, Jie; Chen, Guang (Frontiers in Oncology, 2020)
Abstract: Background: Gross strap muscle invasion (gSMI) in patients with differentiated thyroid cancer (DTC) was defined as high-risk recurrent group in the 2015 American Thyroid Association guidelines. However, controversy persists because several studies suggested gSMI had little effect on disease outcome. Herein, a systematic review and meta-analysis was conducted to investigate impact of gSMI on outcome of DTC. Methods: A systematic search of electronic databases (PubMed, EMBASE, Cochrane Library, and MEDLINE) for studies published until February 2020 was performed. Case-control studies and randomized controlled trials that studied the impact of gSMI on outcome of DTC were included. Results: Six studies (all retrospective studies) involving 13639 patients met final inclusion criteria. Compared with no extrathyroidal extension (ETE), patients with gSMI were associated with increased risk of recurrence (P=0.0004,OR, 1.46; 95% CI: 1.18 to 1.80) and lymph node metastasis (LNM) (P<0.00001,OR 4.19;95% CI. 2.53 to 6.96). For mortality (P=0.34,OR 1.47;95% CI:0.67 to 3.25), ten-year disease-specific survival (P=0.80, OR 0.91;95% CI:0.44 to 1.88) and distant metastasis (DM) (P=0.21, OR 2.94;95% CI. 0.54 to 15.93), there was no significant difference between gSMI and no ETE group. In contrast with maximal ETE(extension of the primary tumor to the trachea, esophagus, recurrent laryngeal nerve, larynx, subcutaneous soft tissue, skin, internal jugular vein, or carotid artery), patients with gSMI were associated with decreased risk of recurrence (P<0.0001,OR, 0.58; 95% CI: 0.44 to 0.76) , mortality (P=0.0003,OR 0.20;95% CI:0.08 to 0.48), LNM (P=0.0003,OR 0.64;95% CI. 0.50 to 0.81) and DM (P=0.0009,OR 0.28;95% CI. 0.13 to 0.59). Conclusions: DTC patients with gSMI had a higher risk of recurrence and LNM than those without ETE. However, in contrast with maximal ETE, a much better prognosis was observed in DTC patients with only gSMI.